PENGARUH TERAPI MUSIK TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST OPERASI FRAKTUR - Harliani Harliani; Eka Surtilah; Muhammad Nur (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2023)
Introduction: Fractures are fractures commonly caused by trauma or physical activity. One of the signs and symptoms of a fracture is pain. Pain in people with fractures is usually sharp and piercing, pain is also commonly caused by spasms of muscles or pinched sensory nerves. The pain felt after undergoing surgical surgery will increase as the influence of anesthesia decreases. One of the non-pharmacological treatments is the administration of music therapy. Music therapy can reduce pain, this is done to distract the client. The purpose of this study was to determine the effect of decreasing the degree of pain in postoperative fracture patients after being given music therapy. Research Methods: This research is a literature study method. The secondary data source is in the form of articles taken from 3 databases (Google Schoolar, Researchgate and Portal Garuda). The criteria for the article being reviewed are a publishing time span of 5-10 years, in Indonesian language, full text available and has been indexed. Articles worthy of review are as many as 10 articles. Results and Analysis: 10 articles explained that music therapy has an effect on reducing the intensity of pain in postoperative fracture patients. Discussion and Conclusion: Based on the explanations that have been put forward that music therapy has an effect in reducing the intensity of pain in postoperative patients.